Personal Trust and System Trust in the Sharing Economy: A Comparison of Community- and Platform-Based Models - Gruber, Sabine (Frontiers in Psychology, 2020)
Currently, new business models created under the keyword of sharing economy differ a lot, just as they differ in the formation of trust. If and how trust can be created, is shown by a comparison of two different examples, which already diverge in their founding philosophy. The chosen example for community-based economy, community supported agriculture (CSA), has no trust in the capitalist system anymore, hence it distances itself and creates its own model, which is implemented within rather small groups where trust is created by personal relations. Contrarily, the example for platform economy, the accommodation provider Airbnb, shows trust in the system and pushes some development using technological innovations, namely platform applications, and promotes for trust and confidence in technology and system progress. For the conceptual analysis the distinction between personal and system trust, made by Niklas Luhmann, is adopted. The analysis describes two different modes of trust formation, how they stress distrust or improve trust. Grounded on this analyses a hypothesis about generally applicable principles on trust formation processes in varying models of sharing economy is formulated.